Etanercept with IVIg for acute Kawasaki disease: a long-term follow-up on the EATAK trial. (12th April 2023) - Sagiv, Eyal; Slee, April; Buffone, Ashley; Choueiter, Nadine F.; Dahdah, Nagib S.; Portman, Michael A.
Abstract: Background: The Etanercept as Adjunctive Treatment for Acute Kawasaki Disease, a phase-3 clinical trial, showed that etanercept reduced the prevalence of IVIg resistance in acute Kawasaki disease. In patients who presented with coronary artery involvement, it reduced the maximal size and short-term progression of coronary artery dilation. Following up with this patient group, we evaluated the potential long-term benefit of etanercept for coronary disease. Methods: Patients were followed for at least 1 year after the trial. The size of dilated arteries (z-score ≥ 2.5) was measured at each follow-up visit. The z-score and size change from baseline were evaluated at each visit and compared between patients who received etanercept versus placebo at the initial trial. Results: Forty patients who received etanercept (22) or placebo (18) in the Etanercept as Adjunctive Treatment for Acute Kawasaki Disease trial were included. All patients showed a persistent decrease in coronary artery size measurement: 23.3 versus 5.9% at the 6-month visit, 24 versus 13.1% at the 1-year visit, and 20.8 versus 19.3% at the ≥ 2-year visit for etanercept or placebo, respectively, with similar results for decrease in coronary artery z-scores. In a multivariate analysis, correcting for patients' growth, a greater size reduction for patients on the etanercept arm versus placebo was proved significant for the 6-month (p = 0.005) and the 1-year visits (p = 0.019) with a similar end outcome at the ≥ 2-year visit. Discussion: Primary adjunctive therapy with etanercept for children with acute Kawasaki disease does not change the end outcome of coronary artery disease but may promote earlier resolution of artery dilation.